Structured Infographic Worksheet through Lesson Study in Improving Madrasa Students’ Writing Skills in Indonesian Language Subject - Fawaid, Achmad; Solehah, Laili Yetus; Assya'bani, Ridhatullah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
This study examines the implementation of structured infographic worksheets within a lesson study framework to improve the writing skills of 10th-grade Madrasa students in Indonesian language classes. The participants included 30 students from a Madrasa in East Java, selected for their varied proficiency levels to represent a typical class composition. These students often deal with challenges in writing descriptive texts, including difficulties with vocabulary selection, grammatical accuracy, and organizing coherent ideas. This study uses a qualitative approach to evaluate how visual tools like structured infographic worksheets can enhance student engagement, collaboration, and writing performance. Data were collected through interviews guided by structured protocols, detailed observation sheets, and rubric-based analysis of student work, all organized around the lesson study cycle (Plan, Do, See). The data were analyzed using thematic analysis to identify patterns of improvement. The findings reveal substantial enhancements in content organization, language use, coherence, and creativity. When integrated with collaborative lesson study practices, structured infographic worksheets effectively meet the educational needs of Madrasa students and improve their writing skills.